Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1007/bf03030823
|View full text |Cite
|
Sign up to set email alerts
|

Shoreline and coral reef ecosystem changes in gulf of Mannar, Southeast coast of India

Abstract: Changes in shoreline, coral reef and seafloor have been mapped using remote sensing satellite data of IRS LISS-III (1998), IRS LISS-II (1988), Survey of India Topographic sheet (1969), Naval Hydrographic Chart (NHO) 1975 and bathymetry data (1999) with ARC-INFO and ARC-VIEW GIS. The analysis of multi-date shoreline maps showed that 4.34 and 23.49 km 2 of the mainland coast and 4.14 and 3.31 km ~ areas of island coast have been eroded and accreted, respectively, in the Gulf of Mannar. The analysis of multi-date… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The change in the geometric center of gravity of the bay is positively related to the growth rate of the shoreline and the complexity of the shoreline geometry; that is, faster shoreline changes correspond to a greater rate of change in the geometric center of gravity of the bay in space (Lai et al, 2015;Li et al, 2010;Snoussi et al, 2008). Among the coastal areas where socioeconomic activities are more concentrated, the change in the bay shape is mainly affected by reclamation activities (Thanikachalam et al, 2003). After studying the changing features of the structure, development and utilization of the Chinese shoreline, reported that human activity mainly involving land reclamation has far exceeded natural factors and has become the dominant factor, especially in recent decades.…”
Section: Reasons For Variations In the Geometric Shape Of The Baymentioning
confidence: 99%
“…The change in the geometric center of gravity of the bay is positively related to the growth rate of the shoreline and the complexity of the shoreline geometry; that is, faster shoreline changes correspond to a greater rate of change in the geometric center of gravity of the bay in space (Lai et al, 2015;Li et al, 2010;Snoussi et al, 2008). Among the coastal areas where socioeconomic activities are more concentrated, the change in the bay shape is mainly affected by reclamation activities (Thanikachalam et al, 2003). After studying the changing features of the structure, development and utilization of the Chinese shoreline, reported that human activity mainly involving land reclamation has far exceeded natural factors and has become the dominant factor, especially in recent decades.…”
Section: Reasons For Variations In the Geometric Shape Of The Baymentioning
confidence: 99%
“…This would indicate that this coast has been subjected to intense soil erosion and accretion. Thanikachalam and Ramachandran (2003) have also reported an average rate of erosion and accretion of 6.23 and 6.54 m/year respectively along the shore of Rameshwaram island of the adjacent Bay of Bengal. Such soil erosions would definitely affect the reef ecosystem by depositing certain percentage of soil on the reef area.…”
Section: Coral Reef Resourcesmentioning
confidence: 91%
“…Shoreline change is the impact of gain and loss of sediment due to the littoral drift. During northeast monsoon period, littoral currents move towards south alter the rate of change of erosion/accretion (Thanikachalam & Ramachandran 2003). The entire coast of Rameswaram facing the GoM, experiences current in westerly direction throughout the year, except in June and July.…”
Section: Coastal Stabilitymentioning
confidence: 99%